PROPUESTA DE UN PLAN DE MARKETING TURÍSTICO PARA LOS ATRACTIVOS NATURALES DE LA PARROQUIA CHICAÑA, CANTÓN YANTZAZA, PROVINCIA DE ZAMORA CHINCHIPE, 2015 - CAMACHO CUENCA, ERIKA ANABEL (2016)
Today tourism is an essential part of any country's economy therefore it has become a highly competitive activity, so much that tourist destinations located in the same country often compete amongst each other. For this reason the tourism marketing and furthermore tourist promotion, it is essential in the development of tourism of any destination. Ecuador is no exception, as it has implemented a comprehensive model of tourism marketing plan (PIMTE 2014), whose main purpose, increase the number of national and international tourists, increase the supply of quality tourism, increase promotion international as well as to enhance sustainable development and improve tourism competitiveness. In the case of the province of Zamora Chinchipe, the reality is different, because in the canton Yantzaza, Chicaña parish is the same that has a culturally rich variety of flora and fauna, natural attractions such as waterfalls of great scenic beauty and caves that have been formed by nature itself. However, these natural attractions do not have the necessary promotion and dissemination, so could not be enhanced for tourism, creating tourism activity in the sector is low and thus is unable to create a competitive market space. Given this reality chosen to perform this research work "Proposal of a plan for tourism marketing for the natural attractions of the Chicaña parish, canton Yantzaza, province of Zamora Chinchipe, 2015" with the aim of strengthening the tourism activity and thus ensure a better position within the local and national tourism. For this targets to comply with this research were established, so that the following general objective was raised, "Develop a plan for tourism marketing for the natural attractions of the parish Chicaña Region Yantzaza province of Zamora Chinchipe" from which the specific objectives are derived from: To make a diagnosis of the current situation of the natural attractions of the Chicaña parish; Propose a tourism marketing plan for the natural attractions; and to socialize the tourism marketing plan with the authorities of the parish and the community in general. For the development of the methodology, inductive, deductive and descriptive, useful for, selecting and analyzing field data and bibliographic 5 methods and an overview of the problem identified in the parish it was considered, which allowed give way to the respective thereby conclusions and possible recommendations. Besides inventory sheets , summary and ranking of the Ministry of Tourism was used , through which they could assess the current state of the attractiveness and the level of hierarchy obtained from the same well , identified attractions to consider the proposal. In relation to techniques it took into account the interview, which allowed to obtain real information from the respondents; the survey, the same as after sampling went to a certain group of people, where he studied and gathered information that helped solve the problem in research; and direct observation by the potential of the sector which was detected in the study. So it was also necessary the development of the SWOT matrix (Strengths, weaknesses, opportunities and threats), which allowed the current situation in which the parish and its attractions, accordingly several strategies to design the proposal is settled. Its design took into account four strategic objectives in the first plan advertising and promotion is established, the second a training plan for tourism service providers and community, the third, the development of a guidebook and fourth organizational model of a tourist information office. Subsequently conducted the socialization of the thesis project , which was unveiled the results obtained during its development , besides the Parish GAD and the community in general I contribute with suggestions , conclusions and recommendations related to the proposed present Marketing Plan. After work it is concluded that the Chicaña parish has a variety of natural attractions and scenic natural beauty with great tourism potential, ideal for tourists to enjoy direct contact with nature, however, due to disinterest by authorities local, they do not have the necessary promotion and dissemination that would ensure the development of tourism So it is recommended to G.A.D. Chicaña Parish as well as the tourism sector entities involved Yantzaza Canton, taking into account the natural resources within their development plans to encourage progress in the field of tourism; it is also recommended, implement the proposed Tourism Marketing Plan since it has alternatives to promote tourism demand in the sector.